Post Operasi Fraktur Humerus Dextra dengan Evidence Based Teknik Relaksasi Napas Dalam - Ivon Tine Maleke; Ester Lontoh (Yayasan Syalom Cipta Sumikolah, 2025)
Fracture surgery pain makes it difficult for patients to do daily activities. The pain that occurs is caused by bone fractures that injure healthy tissue. Some independent actions that nurses can take to help patients are by using pain management to eliminate or reduce pain. One of the non-pharmacological therapies that can be given to patients who experience pain is deep breathing relaxation. This therapy is one way for nurses to create a therapeutic environment by using themselves as a tool or medium for counseling in order to help others with health problems. To determine the effectiveness of the implementation of breathing relaxation therapy on post-operative pain of humerus fractures. The method used is a case study. The subjects used were post-operative patients with humerus fractures with pain problems. The results of the study with the application of evidence-based nursing deep breathing relaxation techniques carried out for 2 days, found that the level of pain on the first day was on a pain scale of 6, and on the second day decreased to a scale of 2, from the evaluation results it was found that deep breathing relaxation techniques were effective in reducing pain levels. The results of the case study showed that the level of pain after being given deep breathing relaxation technique intervention there was a decrease in pain in the client. To all health workers to provide non-pharmacological therapy in the form of deep breathing relaxation techniques and provide education so that clients can apply this therapy every time they feel pain.